Extremotolerant Gelatinase Enzyme Production by UCM4 Bacterial Strain Isolated from the Rhizospheric Soil of Rhizophora mangle - BK, Paramashree Deepa; Nanjundaiah, Siddaraju M (Asian Journal of Biological and Life Sciences)
Gelatinases are important metalloproteases which specifically act on gelatin. Gelatinase hydrolyze gelatin into polypeptides, peptides and amino acids which can cross the cell membrane to get utilized by the organisms. Gelatinase and collagenase are not only used in chemical and medical field but also in food and basic biological sciences. Since gelatinase has potential applications and high demands, the search for new isolates producing gelatinase with extremotolerant property is significant. In the present study we focus on potential extremotolerant gelatinase production from Cellulosimicrobium funkei strain UCM4 isolated from the rhizospheric soil of Rhizophora mangle from coastal regions of Dakshina Kannada, Karnataka, India. The isolate was tested for extremotolerant property with potential gelatinase production in extreme physiological conditions such as pH, salinity and temperature. The isolate showed 56,500 μg/ml of gelatinase production at its optimum growth conditions. The gelatinase production was increased with increase in pH from 7 to 11 which was between 56,500 μg/ml to 58,888.3 μg/ml. Gelatinase production was observed at temperature ranges from 30°C to 40°C which was between 57,777.2 μg/ml to 55,555 μg/ml, and salinity ranges from 0% to 5% NaCl (w/v) which was between 56,500 μg/ml to 49,999.5 μg/ml. The study revealed that the Cellulosimicrobium funkei strain UCM4 has ability to produce extremotolerant gelatinase and hence UCM4 has its potentiality for industrial scale production of gelatinase enzyme and the results will stand as a base line data for the production and application of gelatinase in future.
Keywords: Enzymes; Gelatinase; Halotolerant bacteria; Rhizospheric soil.